برنامج الموهبة العربية كمفتاح نجاح تدريب فن الكلام في معهد النقاية الإسلامي مادورا - Lailiyah, Selviatul; Mubaligh, Ahmad; Faruq, Muh (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
The aim of this research is to describe the strategies of Arabic speaking skills training at the Annuqayah Islamic Boarding School Madura. The factors that help and factors that hinder the performance of this strategy. This research was conducted using a qualitative descriptive approach. Data collection was carried out by observing the Mauhibah Arabiyah Program, interviews with female supervisors, administrators and students, as well as studying documents. The Miles and Huberman method was used to analyze the data, which consists of four steps: collecting data, classifying it, presenting it, and drawing conclusions from it. The research results show that the speaking arts training strategy in the Mauhibah Arabiyah Program for Annuqayah Islamic boarding school Madura students is achieved in three forms: 1) scientific debate 2) public speaking 3) and story telling. The internal factor that plays a role is female student discipline. External supporting factors are teacher discipline, the existence of special texts, encouragement and supervision of female graduates, as well as in-depth supervision from female administrators and supervisors and the Arab environment. The internal inhibiting factor is the lack of self-confidence of new female students, while the external inhibiting factor is limited educational methods and communication tools. Keywords: Strategy, Speaking Skills, Mauhibah Arabiyah Program